Pimecrolimus cream in the management of patients with atopic eczema - Jonathan M Spergel (Dove Medical Press, 2009)
Jonathan M SpergelDivision of Allergy and Immunology, The Children’s Hospital of Philadelphia Department of Pediatrics, University of Pennsylvania School of MedicineAbstract: Atopic eczema is a common pediatric skin disorder. This review examines the use of pimecrolimus cream in the treatment of acute and chronic stages of the disease. The standard therapy is the treatment of acute flares with topical medications including pimecrolimus. The use of pimecrolimus cream for the first sign and symptoms of atopic eczema reduces the occurrence of flares as defined by the need for topical corticosteroids. The side effects of pimecrolimus cream are mild without any increase of infections or systemic immune suppression.Keywords: pimecrolimus, atopic eczema, long-term management